(untitled) (Revista da EGN, 2023)
The aim of this article is to test the hypothesis that Halford Mackinder and Nicholas Spykman’s geopolitical theories, which sustained the grand strategy of the United States with the implementation of 1946 Truman Doctrine, are still relevant today after their termination. The results indicate that the intellectual matrixes were found in documents of the grand strategy of the United States in two moments. First, in 1992, in the George Herbert Walker Bush’s government’s Defense Planning Guidance document, formulated by the Pentagon, in February 1992. Second, they were found replicated 10 years after in the first term of President George Walker Bush, inaugurated in 2001. In the latter, the theoretical formulations repercussions were depicted in the official documents Quadrennial Defense Review (2001) and the National Security Strategy (2002). The article concluded that the authors’ ideas remain valid to explain and interpret the actions of the United States’ grand strategy in the international scenario.